New age constraints on Neoproterozoic diamicites in Kuruktag, NW China and Precambrian crustal evolution of the Tarim Craton - He, J.; Zhu, W.; Ge, Rongfeng (Elsevier BV, 2014)
The Neoproterozoic Kuruktag Group in the Kuruktag area located in the northeastern Tarim Craton, NW China, contains multiple diamictites in the Bayisi, Altungol, Tereeken and Hankalchough formations. In order to constrain their deposition age and reveal the crustal evolution history of the Tarim Craton, we integrated zircon LA-ICP-MS U-Pb ages and Hf-isotope data from volcanic and sedimentary samples in the Kuruktag Group.Two volcanic rocks in the upper Altungol Formation yield ages of 655.9. ±. 4.4. Ma and 654. ±. 10. Ma, respectively, first constraining the termination of the Altungol diamictite and the beginning of the Tereeken diamictite. A tuffaceous bed in the uppermost Zhamoketi Formation between the Hankalchough and Tereeken diamictites gives a 616.5. ±. 5.9. Ma age, confirming a maximum age boundary for the youngest Hankalchough diamictite. Along with existing isotopic and geochemical data from other Neoproterozoic glaciations in the world, we propose an Ediacaran age for the Hankalchough diamictite, a Marinoan-age for the Tereeken diamictite and a Sturtian-age for the Altungol diamictite.355 groups of U-Pb age data of detrital zircons from the Baysi and Altungol formations define three major age populations: Neoarchean to early Paleoproterozoic group (weak peaks between 2.8 and 2.3. Ga), Paleoproterozoic group (peak at 1898. Ma) and Neoproterozoic group (peak at 805. Ma). The oldest age population indicates the presence of Neoarchean to early Paleoproterozoic magmatism in the Tarim Craton. The age peak at 1898. Ma is consistent with the Paleoproterozoic high-grade metamorphism and anatexis event which should be correlated with the amalgamation of the Columbia supercontinent. The largest age cluster of 900-700. Ma is interpreted to represent the response of the Rodinia supercontinent.The Hf isotopic model age data of detrital zircons indicate five major stages of crustal growth at 3.6. Ga, 3.3. Ga, 3.1. Ga, 2.9. Ga and 2.7. Ga. The fact that most detrital zircons show negative eHf(t) values suggests that their provenances were dominated by reworked crustal materials. The remaining few detrital zircons exhibit positive eHf(t) values, implicating the addition of juvenile crustal materials. In addition, the magmatic zircons with ages of 655. Ma and 616. Ma in our volcanic samples display eHf(t) values from -7.60 to +4.33, suggesting that they have different magma sources. According to the parallel Precambrian age distribution and Neoproterozoic stratigraphy, we propose that the Tarim Craton had a close relationship with the Yangtze Craton in Rodinia.